Pengaruh Cultural Branding, Employee Engagement, dan Teamwork terhadap Kinerja Karyawan: Studi Kasus: Mimpi Manis Restaurant Tegallalang - Dewi, Ni Kadek Wiwik Desila Serlita; Adriati, I Gst. Ayu Wirati (Ikatan Da'i Indonesia, 2025)
This study aims to determine the effect of cultural branding employee engagement, teamwork partially and simultaneously on employee performance. The sample in this study were 32 employees of Mimpi Manis Restaurant. Data analysis techniques used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, F Test and t Test. From the results of the study, it was found that motivation had a positive and significant effect on employee performance, employee engagement had a positive and significant effect on employee performance, teamwork had a positive and significant effect on employee performance and cultural branding employee engagement and teamwork together had a significant effect on employee performance. Suggestions that can be given by researchers are Mimpi Manis Restaurant is expected to add more ornaments, carvings, and traditional decorative elements to the interior and exterior of the restaurant, make rewards to employees who are active in cultural activities and programs, create more effective coordination channels between departments, periodically provide training for employees.